Development of Webblog-Based Learning Media to Improve Student Learning Outcomes in Chemical Bonding Material - Yudha, Sandy; Asmi, Andalia (Journal of Learning Improvement and Lesson Study, 2023)
This study aims to develop learning media, indicators, and indicators of whether student learning outcomes use webblog learning media developed on chemical bonding material that is higher than the predetermined KKM value. This research is a research development or Research and Development (R&D). By using the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). The sample used in this study were students of class X MIA 1 at SMA Negeri 8 Medan using purposive sampling technique. From the results of the analysis, the media developed by webblog learning. Results The results by the lecturers obtained an average feasibility of 90%, and an average score of material experts was 95%. Thus the learning media developed is valid and very suitable for use as learning media. The learning media developed were then tested on students to see students' chemistry learning outcomes. Testing was carried out using 1 experimental class which was carried out with webblog learning media. The hypothesis test shows that the average student learning outcomes of the experimental class are 78.29 with a minimum completeness criteria (KKM) 75. Based on statistical analysis at the 5% significance level it can be stated that the student learning outcomes using the developed webblog media are higher than the KKM values that have been set.